Plan de marketing para el posicionamiento de productos agroturísticos en la Provincia de Manabí - Mendoza Vergara, Flerida María (2020)
This work was descriptive-exploratory in nature and had the main objective of designing a marketing plan for the positioning of agro-tourism products in the province of Manabí. Four phases were proposed for this; The first was to carry out a tourist diagnosis using techniques such as bibliographic review and field visits, resulting in accessibility deficiencies, basic services, and lack of support for the proper management, promotion, and marketing of agro-tourism products. In the second phase, an analysis of the demand was developed through the application of 384 surveys, obtaining as a result that 34.11% of the visitors have an average age of 18 to 24 years, 11.72% reside in Guayaquil and 46.61 travel with the family. %. In the study of supply, it was identified that establishments dedicated to providing accommodation, food and beverages prevail, and some work informally. The third phase consisted of the characterization of the agritourism products of the province, the Grandfather Route, the Enchantment Route, the Route of the Senses and the Circuit of Fine Cocoa of Aroma, located in the central west zone of Manabí, were identified. In the fourth phase, the marketing plan was structured, establishing the objectives, the mission, the vision, the brand and the strategies, thus allowing the development of sixteen development projects with their respective budgets and execution schedules in the medium and long term.